PKZ, a Fish-Unique eIF2α Kinase Involved in Innate Immune Response - Wu, Chuxin; Zhang, Yibing; Hu, Chengyu (Frontiers in Immunology, 2020)
PKZ is a novel and unique eIF2α protein kinase identified in fish. Although PKZ is most homologous to PKR, particularly in the C-terminal catalytic domain, it contains two N-terminal Z-DNA-binding domains (Z1 and Z2) instead of the dsRNA binding domains (dsRBDs) in PKR. As a novel member of eIF2α kinase family, the available data suggest that PKZ has some distinct mechanisms for recognition, binding and B-Z DNA transition. Functionally, PKZ seems to be activated by the binding of Z to Z-DNA and participates in innate immune responses. In this review, we summarize the recent progress on fish PKZ.